MARKETING STUDIES OF VETERINARY PHARMACY ORGANIZATIONS ASSORTMENT - A. A. Deltsov; I. V. Kosova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Nowadays there is an active growth of veterinary pharmacy organizations and consumed medicinal drugs for veterinary use. Content-analysis showed that there was an insufficient number of studies devoted to the activity of veterinary pharmacies. The purpose of our work was the analysis of correspondence of range fullness of veterinary pharmacies to the contemporary state of pharmaceutical market of drugs for veterinary use. Veterinary clinics and pharmacies of Moscow and Moscow oblast were the object of our study. We have applied sociological methods (questionnaire, interview), marketing and statistic analysis methods. We have established that liquid dosage forms (53%) occupy the biggest part of drugs in the State Registry of Veterinary Drugs. Solutions occupy 68% of this amount. Antimicrobial drugs for systematic use (40%) are the most numerous drugs from pharmacotheraperutic group represented in the State Registry. Assortment of veterinary drugs is targeted mainly on a farm livestock (more than 50%). 58% of the market share is domestic drugs. Principal commodity groups which are released by veterinary pharmacies are feed-stuff (31%) and drugs (30%). Pharmacy organizations does not have sufficient number of drugs in their assortment (fullness coefficient 7.9%) which speaks about nonconformity of the assortment fullness.